Efficacy and tolerability of adjuvant therapy in ≥70-year-old patients with T3N0M0 colorectal cancer: An observational study. (April 2020) - Sakin, Abdullah; Yasar, Nurgul; Sahin, Suleyman; Arici, Serdar; Secmeler, Saban; Can, Orcun; Geredeli, Caglayan; Demir, Cumhur; Cihan, Sener
Background: This study aimed to retrospectively investigate the efficacy and tolerability of adjuvant chemotherapy in ≥70-year-old patients with stage IIA (T3N0M0) colorectal cancer. Methods: Lymphovascular invasion, perineural invasion, margin positivity, dissected lymph node count of <12, and presence of perforation/obstruction were accepted as risk factors. Those patients with at least one risk factor were regarded as having high risk. Results: The study included 168 patients, among which 95 (56.5%) were male and 73 (43.5%) were female. The median age of patients was 73 years (range: 70–94). One hundred one (60.1%) patients were identified to have high risk. Eighty-one (87%) patients received 5-flourouracil+leucovorin and 12 (13%) patients received capecitabine regimens as adjuvant chemotherapy. The patients receiving capecitabine regimen had significantly higher rates of dose reduction at initiation and during the treatment. Among low-risk group, there was no statistically significant difference between patients with and without adjuvant chemotherapy in terms of disease-free survival or overall survival (p = 0.528 and p = 0.217, respectively). In high-risk group, patients receiving adjuvant chemotherapy significantly differed from those not receiving adjuvant chemotherapy in terms of median disease-free survival and overall survival (p = 0.009 and p < 0.001, respectively). While the grade, lymph node status, and adjuvant chemotherapy were identified as the most significant independent factors for disease-free survival, the most significant factors for overall survival were the age, Eastern Cooperative Oncology Group performance status, adjuvant chemotherapy, and recurrence. Conclusion: The findings of our study showed improved disease-free survival and overall survival in high-risk ≥70-year-old patients who received adjuvant chemotherapy due to T3N0M0 colorectal cancer. We believe that 5-flourouracil+leucovorin or capecitabine regimens should be recommended for these older high-risk patients who could receive adjuvant chemotherapy regardless of age.